Kudoa ajurutellus n. sp. (Multivalvulida: Kudoidae), a parasite of the skeletal musculature of the Bressou sea catfish, Aspistor quadriscutis, in northeastern of the State of Pará - Neto, José Pompeu Araújo; Cardim, Joyce; Da Silva, Diehgo T.; Hamoy, Igor; Matos, Edilson; Abrunhosa, Fernando (Zootaxa, 2020)
Kudoa ajurutellus n. sp. (Multivalvulida: Kudoidae) is described as a parasite of the Bressou catfish, Aspistor quadriscutis (Siluriformes) collected at Ajuruteua beach, northeastern Pará, Brazil. The new species is described based on the morphology of the spores and the sequence of the 18S rDNA. This parasite was found only in the skeletal muscular tissue of fish hosts. In the apical view, the spores were pseudo-quadrangular in shape, with rounded borders, and four symmetrical capsules. The spores are 6.63±0.53 μm in length and 8.16±0.75 μm in width. The polar capsules are piriform, 3.45±0.30 μm in length and 1.87±0.15 μm in width. The phylogenetic analysis based on the sequence of the 18S rDNA gene indicated that the new species is clearly distinct from all other Kudoa species, and that the degree of differentiation is constant with the existence of a new species of the genus Kudoa. This is the first marine Kudoa species recorded in northeastern of the State of Pará.